2022
DOI: 10.1049/cit2.12098
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for distance measurement using stereo camera

Abstract: Distance estimation can be achieved by using active sensors or with the help of passive sensors such as cameras. The stereo vision system is generally composed of two cameras to mimic the human binocular vision. In this paper, a Python‐based algorithm is proposed to find the parameters of each camera, rectify the images, create the disparity maps and finally use these maps for distance measurements. Experiments using real‐time images, which were captured from our stereo vision system, of different obstacles po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Algorithms that draw inspiration from nature are widely employed nowadays in a variety of fields, such as atom optimization [ 52 ], Python-based algorithm [ 53 ], and swarm‐intelligence optimization algorithm [ 54 ]. The MFA is an optimization method that uses the natural selection theory.…”
Section: Methodsmentioning
confidence: 99%
“…Algorithms that draw inspiration from nature are widely employed nowadays in a variety of fields, such as atom optimization [ 52 ], Python-based algorithm [ 53 ], and swarm‐intelligence optimization algorithm [ 54 ]. The MFA is an optimization method that uses the natural selection theory.…”
Section: Methodsmentioning
confidence: 99%
“…Adil proposed a Python-based algorithm to find the parameters of the binocular camera, create disparity maps, and use these maps for distance measurements. Experiments showed that 99.83% measurement accuracy was obtained at 100 cm, with a processing time of less than 0.355 s [49]. These studies explored an approach to measuring objects using a binocular stereo camera and supported a feasible way to measure the wood log using the image detection method with a binocular stereo camera.…”
Section: Introductionmentioning
confidence: 93%
“…Wang et al [20] provided the analysis of the guidelines of bionic eyes using flexible stereo vision equipment. Adil et al [21] designed a novel distance measurement algorithm using stereo vision. The accuracy and the quality of disparity map were most important indices for evaluating the results.…”
Section: Perception Accuracy Of Stereo Visionmentioning
confidence: 99%
“…Adil et al. [21] designed a novel distance measurement algorithm using stereo vision. The accuracy and the quality of disparity map were most important indices for evaluating the results.…”
Section: Related Workmentioning
confidence: 99%